INNOVATION IN EDUCATION: A REVIEW OF THE LITERATURE ON METHODS AND PRACTICES - Loso Judijanto (Indonesian Journal of Education (INJOE), 2025)
This research reviews existing literature on innovations in education, focusing on methods and practices implemented to improve student learning outcomes and the learning process. The main findings show that innovations such as project-based learning, flipped classroom and educational technology can increase student participation and motivation. In addition, approaches that prioritise personalisation and differentiation of education are effective in meeting individual needs and maximising each student's potential. However, the study also identified challenges in implementing innovations, including the need for adequate infrastructure, teacher training and acceptance of change. Support from various parties, including the government and educational institutions, is considered essential to ensure the success and accessibility of innovations across the board.